(untitled) - Đặng, Kim Quốc Chương (Cần Thơ, 2011)
To help non-major English learners in this centre were able to enhance, develop their speaking fluency and encourage learners to apply this activity in their social communication. Also, via the topic-based presentation, teachers perceived, paid attention to its usage and applied it in their teaching speaking for students at schools, centre for foreign languages in Can Tho city, Viet Nam.
Keywords: Speaking skills,Kỹ năng nói